A High‐Speed and Low‐Power Multistate Memory Based on Multiferroic Tunnel Junctions. (13th March 2018) - Huang, Weichuan; Zhao, Wenbo; Luo, Zhen; Yin, Yuewei; Lin, Yue; Hou, Chuangming; Tian, Bobo; Duan, Chun‐Gang; Li, Xiao‐Guang
Abstract: Ferroic‐order‐based devices are emerging as alternatives to high density, high switching speed, and low‐power memories. Here, multi‐nonvolatile resistive states with a switching speed of 6 ns and a write current density of about 3 × 10 3 A cm −2 are demonstrated in crossbar‐structured memories based on all‐oxide La0.7 Sr0.3 MnO3 /BaTiO3 /La0.7 Sr0.3 MnO3 multiferroic tunnel junctions. The tunneling resistive switching as a function of voltage pulse duration time, associated with the ferroelectric domain reversal dynamics, is ruled by the Kolmogorov–Avrami–Ishibashi switching model with a Lorentzian distribution of characteristic switching time. It is found that the characteristic resistance switching time decreases with increasing voltage pulse amplitude following Merz's law and the estimated write speed can be less than 6 ns at a relatively higher voltage. These findings highlight the potential application of multiferroic devices in high speed, low power, and high‐density memories. Abstract : Multi‐nonvolatile resistive states with a high switching speed of 6 ns and a low write current density of about 3 × 10 3 A cm −2 are demonstrated in the crossbar‐structured memories based on La0.7 Sr0.3 MnO3 /BaTiO3 /La0.7 Sr0.3 MnO3 multiferroic tunnel junctions, which highlight the potential application of multiferroic devices in high‐performance nonvolatile memories.